Review on pharmacological therapies for management of gestational diabetes - Shabnam Akram; Safia Bibi (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2023)
The prevalence of Gestational Diabetes Mellitus (GDM) is increasing and is closely linked to numerous negative pregnancy outcomes. To mitigate these risks, early identification and management of GDM is critical. Treatment for GDM aims to maintain normal blood sugar levels and typically includes glucose monitoring, adjustments to diet, lifestyle changes, moderate physical activity, and medication as necessary. Insulin administration is generally the preferred choice for pharmacotherapy, but oral drugs such as metformin or glyburide may also be appropriate. Compared to glyburide, which has been linked to higher birth weight, neonatal hypoglycemia, raising the risk of shoulder dystocia, and necessitating a caesarean delivery, metformin is seen to be a safe first-line therapy. It should be emphasized that some expecting mothers choose complementary and alternative therapies, such as traditional herbal supplements and treatments. This review article will address present pharmacological options and considerations associated with treating GDM.